A comparison of cemented and cementless intra-neck curved stem use during hip-preserving reconstruction following massive femoral malignant tumor removal - You, Qi; Lu, Minxun; Min, Li; Luo, Yi; Zhang, Yuqi; Wang, Yitian; Zheng, Chuanxi; Zhou, Yong; Tu, Chongqi (Frontiers in Oncology, 2022)
BACKGROUND: Patients that undergo massive femoral malignant tumors (MFMT) resection often exhibit shortened femoral metaphyseal juxta-articular segments. The use of a customized femoral endoprosthesis (CFE) with an intra-neck curved stem (INCS) has emerged as a viable reconstructive surgical strategy for these individuals. Relative to a cemented INCS, it remains unclear as to whether cementless INCS use is associated with improvements in functionality or reconstructive longevity. As such, the present study was conducted to compare functional outcomes, endoprosthetic survival, and endoprosthesis-related complication rates in patients undergoing cemented and cementless INCS implantation. METHODS: Twenty four patients undergoing lower limb salvage and reconstructive surgical procedures utilizing cemented or cementless INCS endoprostheses were retrospectively included. Patient functional outcomes, endoprosthetic survival, and complication rates were compared as a function of age, diagnosis, length of femoral resection, residual proximal femur length, Musculoskeletal Tumor Society (MSTS) scores, visual analog scale (VAS) scores, and rates of implant breakage, periprosthetic infections, periprosthetic fractures, and aseptic loosening. RESULTS: The mean follow-up was 56 months. Significant differences in the length of femoral resection (p＜0.001) and residual proximal femur length were observed (p＜0.001) between the cemented and cementless INCS groups. There were no differences in overall patient survival and aseptic loosening-associated endoprosthesis survival in the cemented and cementless groups. None of the included patients experienced periprosthetic fractures, infections, or implant breakage. Average respective MSTS and VAS scores did not differ between groups. CONCLUSION: For patients undergoing treatment for MFMTs, the use of a CFE with an INCS has emerged as a viable approach to hip-preserving reconstructive surgery. With appropriately designed individualized rehabilitative programs, good functional outcomes can be achieved for these endoprostheses, which are associated with low complication rates. Moreover, the selection between cemented or cementless INCS in the clinic should be made based on patient-specific factors, with cementless INCS implementation being preferable in younger patients with good quality bone, the potential for long-term survival and the osteotomy site near the lesser trochanter, whereas cemented INCS use should be favored for individuals who are older, have a shorter life expectancy, or have poor bone quality.